PROGRAM PENGEMBANGAN POTENSI DAN PEMBERDAYAAN MELALUI PENDIDIKAN LIFE SKILL,” (PENGEMBANGAN LIFE SKILL PENGHUNI PANTI ASUHAN AT-TAQWA MUHAMMADIYAH KENAGARIAN III KOTO KEC. RAMBATAN KABUPATEN TANAH DATAR) - Irwandi Irwandi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2018)
Orphans in Islam have a specific position in Islam as contextually religious already exists in the Letter Alma'un verses 1-7, in this context we are expected to be able to empower orphans especially to develop themselves thoroughly and specifically which leads to the development of life skills intended for self-development so that it can be useful for themselves, society and nation and religion. Methods of self-development Through education, it forms the character of children and understands their nature, the essence of their lives, the nature of community, religion and state. Seeing such conditions, the orphanage plays an important role in educating foster children in the form of safe skills to minimize the condition of children who are unable to continue their education, At-Taqwa Muhammadiyah Orphanage Nagari III Koto is one of the orphanages registered in the Social Service and the Tanah Datar district labor force with a total of 56 foster children with a total of 3 caregivers, is a valuable asset in fostering life that leads to education patterns that are oriented towards the lifeskill. The method used in this study is a descriptive method with a qualitative approach, with the focus of the discussion is the Potential and Empowerment Development Program through Life Skill Education at the orphanage At-taqwa Muhammadiyah kenagarian III koto Kec. Rambat Tanah Datar Regency.